ABP: a low-cost, energy-efficient clustering algorithm for relatively static and quasi-static MANETs. (27th January 2009) - Gavalas, Damianos; Pantziou, Grammati; Konstantopoulos, Charalampos; Mamalis, Basilis
Clustering techniques have been proposed to construct hierarchies of nodes inside Mobile Ad Hoc Networks (MANETs) thereby increasing their scalability and manageability and reducing the amount of maintained routing information. Herein, we introduce a distributed clustering algorithm that uses both location and energy metrics for cluster formation. Our proposed solution addresses cluster stability, manageability and energy efficiency issues. Unlike existing active clustering methods, our algorithm relieves the network from the unnecessary burden of control messages broadcasting, especially for relatively static and quasi-static network topologies. The efficiency, scalability and competence of our algorithm against alternative approaches have been demonstrated through simulation results.